Mixed Weibull distribution model of DC protection system based on entropy weight method. (September 2020) - Wang, Ting; Chen, Kun; Zhang, Kanjun; Du, Zheng'an; Li, Jun; Dai, Di
Abstract: By analyzing the blocking event of DC converter station of the State Grid Corporation in recently ten years, it can be concluded that the sampling system failure, secondary circuit fault, board fault, host fault, etc. of the protection system caused more than 10% of the DC system blockings, which have seriously threatened the normal operation of DC system. Towards this end, this paper makes a statistical analysis of the operation defects of high-voltage direct current (HVDC) transmission protection in Hubei Company in the past five years. A mixed Weibull distribution model method based on entropy weight method is proposed. By using this method, the reliability curve and average defect interval time ( MTBF ) of the DC protection system are obtained. Combined with the actual situation of the converter station, the DC protection system of the converter station is evaluated, which provides an important guiding basis for the subsequent maintenance, system transformation, and replacement of the converter station.